Pendaftaran Merek Kolektif Sentra Gudeg Wijilan Di Kota Yogyakarta Ditinjau Dari Undang–Undang Nomor 20 Tahun 2016 Tentang Merek Dan Indikasi Geografis - Sherina Puspita Salsa Bela; Shakira Wandari Putri; Sheila Noor Baity; Budi Agus Riswandi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Yogyakarta City is an area known as a tourist destination for tourists who have culinary tourism attractions, one of which is gudeg. Gudeg as an icon as well as a typical culinary of Yogyakarta City is also preserved by the community and supported by the Government with the establishment of gudeg industry centers, including the Wijilan Gudeg Center as a popular gudeg culinary tourism center. Although known as the Wijilan Gudeg Center, the fact is that most gudeg traders in the area have not registered their brands with the Ministry of Law and Human Rights through the Directorate General of Intellectual Property Rights due to the lack of knowledge of gudeg traders regarding the importance of legal protection for gudeg brands. The method used in this study is the empirical juridical method through a statute approach which is then analyzed using descriptive analysis. The results of the study indicate that gudeg traders in the Wijilan Gudeg Center area have the potential to register brands collectively which are used as an alternative to legal protection for brands for gudeg traders according to Law Number 20 of 2016 concerning Brands and Geographical Indications.